The role of optimism bias and public trust in the goverment on non-compliant behaviour with health protocols - Agustina, Gita Nuraini; Ardi, Rahkman (Universitas Muhammadiyah Surakarta, 2021)
Abstract. The occurrence of risky actions by the community and the inconsistencies of government policies regarding Covid-19 pandemic led to community non-compliance with the health protocols. The purpose of this study was to investigate the role of unrealistic optimism bias and public trust to the government towards non-compliance behavior during the COVID-19 pandemic. This study was a quantitative study with data collection procedures using the survey method. The three questionnaires i.e. the unrealistic optimism bias, public trust in government, and non-compliance behavior, have been adopted from the previous studies and validated using CVI for the purpose of this study. There were 740 participants ranging between 18-25 years old. Stepwise regression analysis was conducted. The resultsshowed that the unrealistic optimism bias and public trust to the government simultaneously contributed to non-compliance behavior in which the unrealistic optimism bias had the highest contribution to noncompliance behavior during the COVID-19 pandemic. This study implies that the government and intervention agencies need to pay attention to the factors of cognitive biases by the individuals and public trust issues for improving the public adherence to the health protocols.Keywords: COVID-19 pandemic; non-compliance behavior; public trust in government; unrealisticoptimism bias.